This Way Brouwn: Arkivfeber og den vordende fremtid - van der Meijden, Peter (Peripeti, 2010)
Around the time of the emergence of the neo-avant-garde, in the early 1960s, conceptual artist Stanley Brouwn created This Way Brouwn, an apparently archival work that critically engages with matters of conservation, but with the pre-war avant-garde’s focus on the future as well. The work and its positioning in time is here discussed in the light of Jacques Derrida’s essay ”Archive Fever”